AKSELERASI PENGETAHUAN MASYARAKAT DI PULAU DOMPAK TENTANG BAKAU SEBAGAI SUMBER HIDUP - Siti Arieta; Teguh Setiandika Igiasi; Taufiqurrachman Taufiqurrachman; Annissa Valentina; Casiavera Casiavera; Nikodemus Niko (Universitas Mataram, 2022)
The community service activity was initiated by the Department of Sociology team, Faculty of Social and Political Sciences, Universitas Maritim Raja Ali Haji with partners of Dompak Village, Tanjungpinang City. The problem of partner to be solved is the lack of attention of the community in utilizing mangrove to meet the needs of daily life. Furthermore, the program is in the form of socialization about mangroves as a source of livelihood and training on making products with raw materials for mangrove fruit, namely soap and coffee products. The program aims to re-express community knowledge about the use of mangroves. On Dompak Island, people's knowledge about the use of mangroves is only used as charcoal for cooking. This activity is carried out by two methods, namely socialization and training. Socialization was carried out to provide awareness about the importance of mangroves for the lives of the people of Dompak Island. Then the training focused on making mangrove coffee products and mangrove soap. The program is carried out in the form of socialization and training on making products in the form of coffee and soap made from the basic ingredients of mangrove fruit. From this training, the Dompak community is expected to be independent in utilizing mangroves as a source of life. Based on the results of socialization activities and training on the use of mangrove fruit as a livelihood support, there are two products produced, namely mangrove coffee products and mangrove soap. The enthusiasm of the participants who attended and listened to this socialization and training activity can be seen from their participation in direct practice of making soap and coffee from mangroves. The program provides new knowledge for the Dompak community in relation to the use of mangroves as a source of daily livelihood.